Women’s Word Use in Pregnancy: Associations With Maternal Characteristics, Prenatal Stress, and Neonatal Birth Outcome - Schoch-Ruppen, Jessica; Ehlert, Ulrike; Uggowitzer, Franziska; Weymerskirch, Nadine; La Marca-Ghaemmaghami, Pearl (Frontiers in Psychology, 2018)
Background: Experiencing high levels of stress during pregnancy can impair maternal well-being and foetal development. Consequently, unbiased assessment of maternal psychological state is crucial. Self-report measures are vulnerable to social desirability effects. Thus, implicit measures, such as word choice analysis, may offer an alternative. Methods: In this longitudinal online-study, 427 pregnant women described their emotional experiences in writing and additionally responded to self-report questionnaires assessing symptoms of prenatal stress and depression. The written texts were analysed with a computerised text analysis program. After birth, 253 women provided information on birth outcome. Results: Word use differed significantly depending on maternal socioeconomic (e.g., marital status) and pregnancy-related characteristics (e.g., parity). Prenatal stress and depressive symptoms were associated with more frequent use of negative emotion words and words of anxiety, as well as with less first-person plural, but not singular pronoun use. Negative emotion and cognitive mechanism words predicted birth outcome, while self-report measures did not. Conclusion: In addition to self-report measures, word choice may serve as a useful screening tool for symptoms of depression and stress in pregnant women. The findings on pronoun use may reflect women’s changing experience of self-identity during the transition to motherhood.